Exercise training reduces cardiac fibrosis, promoting improvement in arrhythmias and cardiac dysfunction in an experimental model of chronic chagasic cardiomyopathy - Improta-Caria, Alex Cleber; Nonaka, Carolina Kymie Vasques; Daltro, Pâmela Santana; Azevedo, Carine Machado; Barreto, Breno Cardim; Carvalho, Gisele Batista; Vasconcelos, Juliana Fraga; Souza, Bruno Solano de Freitas; Macambira, Simone Garcia; Soares, Milena Botelho Pereira (Frontiers in Physiology, 2025)
BackgroundChagas disease, caused by the parasite Trypanosoma cruzi, is associated with inflammation and fibrosis, which characterizes chronic Chagasic cardiomyopathy (CCC). CCC manifests as arrhythmias, hypertrophy or dilation of the left ventricle, and it may progress to heart failure. Therefore, interventions are needed to slow the progression of CCC. Aims: We investigated the effects of exercise training in an animal model of CCC.MethodsC57BL/6 mice infected with Trypanosoma cruzi were submitted to a progressively treadmill exercise training protocol. The cardiac function was evaluated by echocardiogram and electrocardiogram. RT-qPCR and morphometric analyses were performed on samples of cardiac tissue to quantify inflammation and fibrosis.ResultsEKG analysis confirmed that all infected mice developed arrhythmias, with different degrees of severity. Exercise improved arrhythmias in 43.75% of chagasic trained mice, and the remaining mice did not show any alteration in EKG. The untrained chagasic group had no improvement in arrhythmias. The ventricular compliance in chagasic trained mice increased, as revealed by the reduction in isovolumetric relaxation time when compared to untrained mice. Exercise induced the reduction of gene expression of TGF-β, TNF-α, IL-1β, IL-6 and MMP-9 and reduced fibrosis in the heart tissue of chagasic mice.ConclusionExercise reduced fibrosis in the heart and skeletal muscle, favoring the improvement of arrhythmias, and augment of cardiac complacency in mice with CCC, in addition to decreasing the expression of profibrotic and proinflammatory genes in the heart.